"Fleshy" Skin Cellulitis: A Triggering Factor for ANCA Associated Vasculitis - Sim, Chun Yang; Ruslinda, Mustafar; Lydia, Kamaruzaman; Kong, Wei Yen; Rozita, Mohd; Rizna, Cader (MyMedR, 2019)
A 59-year-old lady with underlying hypothyroidism presented with acute contact dermatitis progressed to cellulitis with superimposed bacterial infection and acute kidney injury. She responded to initial management with antibiotics, but a week later, she had cutaneous and systemic vasculitis. Her skin biopsy consistent with immune-mediated leuko-cytoclastic vasculitis and her blood test was positive for cytoplasmic-anti-neutrophil cytoplasmic antibody (c-ANCA). A diagnosis of ANCA-associated vasculitis was made and she was treated with immunosuppressant with plasmapheresis and hemodialysis support for her kidney failure. Despite aggressive measures, the patient succumbed to her illness. This case report demonstrates that soft tissue infection could trigger the development of ANCA-associated vasculitis whilst a background of hypothyroidism serves as a predisposing factor as both condition were reported separately in a couple of case studies before.